Photojournalism disrupted the view from Australia - Caple, Helen (Disruptions : studies in digital journalism, 2019)
"Photojournalism Disrupted addresses the unprecedented disruptions in photojournalism over the last decade, with a particular focus on the Australian news media context. Using a mixed methods approach, the book assesses the situation facing press photographers and their employers in the supply of professional imagery for news storytelling. Detailed qualitative case studies looking at special events and crisis reporting complement a longitudinal study of sourcing practices around everyday events. Additionally, interviews with industry professionals offer insights into how news organizations are managing significant structural change. Ultimately, the book argues that photojournalism is being reshaped in line with wider industrial disruptions that have led to the emergence of a highly casualized workforce. As a comprehensive study of contemporary photojournalism practices, Photojournalism Disrupted is ideal for scholars and students internationally, as well as (photo)journalists and media professionals"--